ANALISIS PELAYANAN FARMASI PADA KLINIK PRATAMA DAN APOTEK MULIA MEDIKA - Wilda Jamila Suryaman; Hamdan (Economicus, 2024)
The aim of this research is to determine the pharmaceutical services available at the Pratama Clinic and Mulia Medika Pharmacy. The method used in this research is the Qualitative Method. The data collection technique for this research uses interview, observation and documentation methods. Data analysis in this research uses data reduction, data presentation and drawing conclusions from respondents. The results of this research show that the pharmaceutical services provided at the Pratama Clinic and Mulia Medika Pharmacy have provided good service to patients.